Development of auxiliary equipment for 1 seater drag buggy - Mohd Khalis Aizat, Abd Aziz (2008)
Development of Auxiliary Equipment for one seater drag buggy is one of the Mechanical Faculty project and this task of the project must be completed by Mechanical Engineering student. Project Objective is to design brake pedal, fuel pedal, piping and tank attachment and to fabricate the mechanical part of the system. This project must be complete to ensure the whole system of the drag buggy car can be applied. Several aspects must be consider when make analysis such as strength analysis, dimension analysis selection concept analysis. All the system must be done without collide or bother any system to avoid another system failure when applying. So, efficiency is important criteria to make this system go well. Then, fabrication and modification process should be making properly. If any problem occurs, it will become dangerous for the driver. Another thing that should have to develop this project is knowledge, skills and interest feeling. Without that, this project can’t be going far. So, all the process must be follow on the flow and all system should be making correctly and properly for the perfection.